Non-contact measurement of glucose in urine by smartphone-based laser refractometry for diabetes monitoring - Amirul Badiuzzaman Sinin; Khairul Fikri Tamrin; Muhammad Hamdi Mahmood (Scientific Reports)
Abstract Diabetes mellitus is a global health issue affecting millions of people and requires regular glucose level monitoring. Current non-invasive methods, such as urinalysis (including colorimetry and biosensors), are primarily laboratory-based and lack user-friendliness, limiting their practicality for continuous glucose monitoring. Although promising, research on smartphone-integrated laser refractometry for glucose detection remains limited. To address this gap, a non-contact, smartphone-based laser refractometer for glucose monitoring was developed. This prototype measures the refractive index of urine by analyzing the refracted length of a laser line, which correlates with fasting blood glucose concentrations. The system uses a smartphone to capture high-resolution images of the laser line generated by total internal reflection through a rod and refraction through the urine sample. Assessments were conducted using controlled glucose concentrations, varying turbidity levels, different samples volume, and shelf-life conditions. Volumetric and shelf-life variations showed no significant impact on results, whereas turbidity assessments revealed a limitation of up to 57 nephelometric turbidity units (NTU). Fasting glucose levels measured from using the developed system were compared with laboratory fasting blood glucose results, yielding a correlation coefficients of 0.89 and a sensitivity of 4.8 mg/dL. The system is low-cost, making it accessible and suitable for telemedicine applications, offering remote glucose monitoring for patients. This approach paves the way for clinically relevant glucose detection in diabetic patients without the need for invasive finger-prick blood sampling.